Electoral Libels: A Comparative Study of the English and Ecuadorian Law of Defamation - Roberto Andrade (UCL Journal of Law and Jurisprudence, 2017)
English and Ecuadorian defamation law have developed very different mechanisms to resolve the tension between the right to freedom of speech and the protection of private life. Ordinarily this would not be too surprising, insofar as it is natural that different countries will have different legal institutions. However, this divergence becomes relevant because both jurisdictions claim to be bound by virtually the same human rights obligations when it comes to speech related to matters of public interest. For this reason, this article focuses on speech issued during electoral campaigns –perhaps the best example of public interest speech- in order to assess how different jurisdictions prioritise between the different rights and interests at play in these kind of defamation cases. For full text, please click here
Keywords: ACHR; ECHR; Comparative Law; Media Law; Defamation